Rethinking Credit and Capital Subsidies to Create Jobs Through MSMEs: The Role of Impact Investment Funds - David A. Robalino; Loubna Bourkane; Amir Ben Ghod Bene (Institute of Labor Economics (IZA), 2025)
The paper discusses the limits of credit and capital subsidies to finance MSMEs in the presence of jobs-related externalities. Using a stylized model of the decision to lend to enterprises with different levels of risk, we show that instruments like credit guarantees are likely to exclude enterprises that have a higher social rate of return and a higher social value than some of those that get access to credit. We also show that pigouvian wage subsidies equal to the value of the jobs externality are unlikely to be an efficient policy instrument; they would need to be firm specific and do not change the distribution of financial risks. We argue that impact investment funds focused on jobs (IIFJ) can be a market mechanism to channel part of existing government subsidies and deal with market failures resulting from both asymmetric information and jobs externalities. Using an extended version of the model that is calibrated to a representative country we show that – if well designed – IIFJ can generate significant welfare gains relative to traditional investment funds because of their impact on jobs.
Keywords: G2; J3; O1; 330; jobs externalities; credit guarantees; pigouvian wage subsidies; impact investment funds